The effectiveness of mindfulness training based on reducing stress on the desire for divorce, blood pressure and sexual satisfaction in betrayed women with high blood pressure - Aghili, Mojtaba; Asghari, Arezou; Ozmaee, Mahdiyeh; Namazi, Mitra (Psychology of Woman Journal, 2022)
The present study investigated the effectiveness of mind training in reducing stress on the desire for divorce, blood pressure, and sexual satisfaction in high blood pressure women. The research method is quasi-experimental with a pre-test and post-test design with a control group. The statistical population included women referred to the cognitive counseling service centers in the 1st district of Tehran in 2018 for marital problems and infidelity. The 30 sample people are randomly selected into two experimental and control groups. People of both experimental and control groups responded to the questionnaires about the desire to divorce Roselet et al. (1986) and the sexual entitlement questionnaire of Halbert (1992), and the blood pressure was recorded using a resistance sphygmomanometer. Then, the mental treatment program to reduce stress was implemented during eight sessions, and each session lasted 90 minutes for the experimental group. However, the control group did not receive any intervention. After the end of the course, both experimental and control groups were tested again with the same questionnaires, and blood pressure was measured using the same sphygmomanometer. The obtained data were used by covariance analysis to test the hypotheses. The results showed that mind training reduces stress, reduces the desire for divorce, and blood pressure, and increases sexual satisfaction in high-blood-pressure cheating women (p<0.01). Mind training increased sexual satisfaction and decreased the desire for divorce and blood pressure. It is suggested to use mind training to promote health, and improve sexual performance and interpersonal relationships of betrayed women.